Deaf Subjects : Between Identities and Places - Brenda Jo Brueggemann (NYU Press, 2009)
In this probing exploration of what it means to be deaf, Brenda Brueggemann goes beyond any simple notion of identity politics to explore the very nature of identity itself. Looking at a variety of cultural texts, she brings her fascination with borders and between-places to expose and enrich our understanding of how deafness embodies itself in the world, in the visual, and in language.Taking on the creation of the modern deaf subject, Brueggemann ranges from the intersections of gender and deafness in the work of photographers Mary and Frances Allen at the turn of the last century, to the state of the field of Deaf Studies at the beginning of our new century. She explores the power and potential of American Sign Language—wedged, as she sees it, between letter-bound language and visual ways of learning—and argues for a rhetorical approach and digital future for ASL literature.The narration of deaf lives through writing becomes a pivot around which to imagine how digital media and documentary can be used to convey deaf life stories. Finally, she expands our notion of diversity within the deaf identity itself, takes on the complex relationship between deaf and hearing people, and offers compelling illustrations of the intertwined, and sometimes knotted, nature of individual and collective identities within Deaf culture.